Impact of new passenger rail stations on ridership demand and passenger characteristics: Hiawatha service case study. Issue 4 (December 2020) - Sperry, Benjamin R.; Dye, Tyler
Highlights: Evolution of ridership at a new station is examined using multi-wave survey data. Demand ramp-up was present with full ridership achieved after three years. Approximately half of riders shifted from existing stations and half were new trips. Findings are instructive to ensure that ramp-up is properly addressed in forecasts. Abstract: The opening of a new station on an existing passenger rail route increases accessibility to rail services, resulting in improved travel conditions for current passengers and stimulating new "induced" demand. However, these changes are not realized immediately, resulting in what is commonly referred to as a demand "ramp-up" period. This paper explores the concept of demand ramp-up and the corresponding impacts on ridership and passenger characteristics in the context of the Milwaukee Airport Rail Station, which opened in January 2005 along an existing Amtrak route between Milwaukee and Chicago. Analysis of ridership data from the new station indicated that the ramp-up period was three years; however, the percentage of steady-state ridership at each year of the ramp-up period was lower than the corresponding figures from other studies. The expected impact of the new station on adjacent stations was generally realized for ridership and access patterns, with approximately half of the new ridership being diverted from other stations while the other half were induced trips. Ridership at the new station was comprised of more business travelers than originally anticipated. However, in general, the other predicted outcomes related to the extent of usage of the station have not been realized after 11 years of operation. The results of this paper are instructive to provide planners and sponsors of passenger rail projects with a better understanding of the extent of demand ramp-up for new stations and how the characteristics of passengers evolve during the ramp-up period.